Some features of compression therapy for varicose veins of the lower extremities of clinical class C2 according to CEAP - V. Yu. Bogachev; B. V. Boldin; P. Yu. Turkin; M. N. Klyuchevskaya (Амбулаторная хирургия)
Introduction. The main method of varicose vein disease treatment is surgical intervention. At the same time, there is a rather large group of patients who postpone surgical treatment indefinitely. In this situation, conservative measures come to the fore, the key one among which is compression therapy.Aim. Study of the immediate effect of compression therapy on venous outflow from the lower extremities in patients with varicose veins and the medium-term results of medical knitwear classes 1 and 2.Materials and methods. The study enrolled 64 patients (mean age 28.3 ± 2.2 years, mean BMI 25.3 ± 4.1) with large saphenous vein reflux to the upper third of the tibia. Blood flow return time and pump force were measured while walking without and with zero, class 1, and class 2 compression knitted garments on.Results and discussion. On photoplethysmography return times without and with zero compression were 18.4 ± 2.2 s and 18.9 ± 1.4 s (p = 0.62), tibial venous pump strength was 3.6 ± 0.3% and 3.4 ± 0.2% (p = 0.57). Wearing a class 1 knitwear significantly increased return time and lower leg muscle venous pump strength to 21.6 ± 1.9 sec and 6.2 ± 1.8% (p < 0.001). Grade 2 knitwear increased return blood-flow time and tibia musculo-venous pump strength to 28.2 ± 2.6 sec and 12.3 ± 1.6%, which was significantly higher (p < 0.001). Global quality of life index according to CIVIQ-14 at baseline and follow-up was 44.3 ± 4.6 and 17.8 ± 3.6 points respectively (p < 0.001) in the class 1 group. Compression Class II had a mean value of 45.1 ± 3.9 and 18.1 ± 4.3 (p < 0.001).Conclusion. In summary, the RAL class 2 standard compression knitted fabric shows better immediate correction of lower leg muscle venous pump function in patients with primary varicose veins compared to the class 1 compression knitted fabric. In the mid-term followup there were no differences in the elimination of initial venous specific symptoms and in the improvement of the global quality of life index between class I and class II knitwear.